If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-6*(x/2) = 6 // - 6
-6*(x/2)-6 = 0
-3*x-6 = 0 // + 6
-3*x = 6 // : -3
x = 6/(-3)
x = -2
x = -2
| -4u+7=4u+7 | | 2x+x-6=3 | | 7(3x-5)=3(x+3)-17 | | m^4-625= | | 34.2/7 | | -0.2w-1.7=-1.1w-0.8 | | x+(24/x)=10 | | 2x^2-14x=-20 | | 7/2/1/2 | | 0.3(z-1.5)=1.1(z+0.5) | | -(9y-1)=-9y+17 | | 4/3/8/9 | | -z+7=-3 | | 4y^2-32y=0 | | (6-4)6+4= | | 3y*2-(7+2y*2)-4y+(y+9)= | | -3y-3=3y+5 | | 3y-3=3y+5 | | 11t=121 | | 10x-4x+3=3(x+6) | | -3y-3=-3y+5 | | 2x-1.9=-0.25x+2.37 | | k^5+4k^4-32k^3= | | -42/3=2a/3+1/3+a/3 | | 12y+4=0 | | (x-6)(x+8)=-3(x-14) | | 427/7 | | 9t+7=-9t-11 | | -4t+9=-10 | | 3x^2+23=74 | | 5x-(2-3x)-5= | | (x-9)(x+2)=-3(x-9) |